Quantification and Substitution: The Abstract Space of Virtual Cinematography. (November 2013) - Jones, Nick
In order to assign space value and enter it into an exchange economy, capitalism works to reduce it to an abstract plan. Writing about this process, Henri Lefebvre coins the term 'abstract space' and describes the logics of this kind of space in detail. These logics are also at work in the digitally animated spaces of virtual cinematography, such as those used in The Matrix Reloaded (Andy and Larry Wachowski, 2003). Creating totalized, predictable spaces and populating them with highly instrumental and manageable digital replacements of actors (sometimes known as synthespians), virtual cinematography takes space and individuals to be open to geometric abstraction. Using Lefebvre's work to interpret this virtual spatial production allows a critical evaluation of the motives and consequences of this kind of computer animation to take place, and emphasizes the manner in which virtual cinematography joins up with other visual systems of spatial representation and quantification.